On Some Properties of Metric F-Structure Satisfying $F^{2k+1}+F=0$ - Lakhan Singh; Shailendra Kumar Gautam (International Journal of Mathematics And its Applications, 2017)
In this paper, we have studied various properties of the F-structure satisfying $F^{2k+1}+F=0$. Where $k$ is positive integer The metric F- structure, $f$ induced on each integral manifold of tangent bundle $l^{*}$ have also been discussed.